Problem Solving - Yahaya, Azizi (2010)
Behaviorist psychologists thought problems ere solved by trail and error and reproducing past responses. Cognitive psychologists were convinced problem-solving wasn’t random but that there was a series of mental processes involved. Problem solving involves mentally working to overcome obstacle that stand in the way of reaching a goal. There are many different ways to represent a problem. A problem can be represented mentally ( in your own mind), orally , in writing, on a computer, and so on. Each type of representation has certain advantages and disadvantages. There key steps of problem solving are problem identification, problem definition and representation, strategy construction, organization of information, allocation of resources, monitoring, and evaluation. In everyday experiences, these steps may be implemented very flexibly, such that various steps may be repeated, may occur out of sequence, or may be implemented interactively. Although well-structured problems may have a clear path to solution, the route to solution may still be difficult to follow. When solving ill-structured problems, the choice of an appropriate problem representation powerfully influences the ease of reaching an accurate solution. Additionally in solving ill-structured problems, people may need to use more than a heuristic or an algorithmic strategy; insight may be required. The problems to be solve ant the tasks to be accomplished are challenging. There is explicit instruction on key ideas such as problem posing, working to achieve a clearly defined problem. Building on the previous work of yourself and others. Transfer of learning and viewing each problem as a learning opportunity. Work to learn thins that will help you in the future. Do metacogintion, do a conscious, considered analysis of the components and the overall process in each challenging problem that you address. All this will help us to get better solving problems.